Worlds of long-term care: A typology of OECD countries. Issue 5 (May 2021) - Ariaans, Mareike; Linden, Philipp; Wendt, Claus
Highlights: 25 OECD long-term care systems are compared and classified by adopting most recent quantitative and institutional indicators. Using an innovative clustering approach, an adjustable long-term care typology of nine and six clusters is developed. The following six types are identified: residual public system, private supply system, public supply system, evolving public supply system, need-based supply system, evolving private need-based system. Abstract: Providing long-term care (LTC) to the elderly is a major challenge for the welfare state. LTC systems differ widely among countries. Due to recent maturation, economization, and marketization processes, earlier LTC comparisons and typologies are no longer suitable to give a comprehensive overview of LTC systems and their major characteristics. In this paper we introduce a new typology of LTC systems in the OECD world, based on most recent OECD data and a unique set of institutional indicators. This typology aims to make LTC systems more comparable to welfare state and healthcare system typologies and thereby improve our understanding of how LTC is embedded in the wider welfare state and how it is related to other welfare state institutions. Based on 24 cluster analyses, we identify six (method-driven) and nine (content-driven) LTC types, which can be adapted in future studies according to the needs. In the six-types solution, we suggest a public supply type (e.g., Sweden), a private supply type (e.g., Germany), a residual public type (e.g., Poland), an evolving public supply type (e.g., Korea), a need-based supply type (e.g., Switzerland), and an evolving private need-based type (e.g., United States).